SOCIAL CRITISISM LANGUAGE IN MANJALI DAN CAKRABIRAWA’S NOVEL BY AYU UTAMI (STYLISTICS ANALYSIS) - Irma Satriani; Inung Setyami (Universitas Sebelas Maret, 2023)
This study aims to describe the language that contains elements of social criticism in the novel Manjali dan Cakrabirawa by Ayu Utami using stylistic theory. The data source of this research is the novel Manjali dan Cakrabirawa by Ayu Utami published by PT. Kepustakaan Populer Gramedia. This research is a qualitative descriptive study. The results showed that the language used to convey Ayu Utami's social criticism in her novel, namely 1) language related to historical events, 2) language embodied in songs, 3) language using foreign terms, 4) language related to mystical elements., 5) language related to eroticism, and 6) language of wordplay/Spoonerism Language.